(untitled) (Journal of Sciences & Technology, 2019)
Landslides constitutes one of the main geological dangers to human being. Proper analysis and suitable modeling of these dangers may reduce accident risks. In this study, we used remote sensing techniques and GIS tools to establish landslide susceptibility map of the East of Constantine. To evaluate the landslide risks in the study area, analytical hierarchy process (AHP) method and Weighted Linear Combination (WLC) were used. In this method, we performed quantification of the factors on a priority basis by pair-wise comparison of the factors. The local data includes slope, slope aspect, elevation, distance from drainage, lithology, distance from faults, precipitation, and Normalized Difference Vegetation Index (NDVI) and springs density. The landslide susceptibility index (LSI) was calculated using the WLC technique based on the assigned weight and rating by AHP method. The results were verified using actual landslide locations (43 location points) where the accuracy rate 61% of predict values and 58 % of success values. The validation results with that indicated suitable agreement between the susceptibility map and the existing data on landslide locations.